2017
DOI: 10.18632/oncotarget.17892
|View full text |Cite
|
Sign up to set email alerts
|

Histone modifications affect differential regulation of TGFβ- induced NADPH oxidase 4 (NOX4) by wild-type and mutant p53

Abstract: Previously, we showed wild-type (WT) and mutant (mut) p53 differentially regulate reactive oxygen species (ROS) generation by NADPH oxidase-4 (NOX4): p53-WT suppresses TGFβ-induced NOX4, ROS and cell migration, whereas tumor-associated mut-p53 proteins enhance NOX4 expression and cell migration. Here, we extended our findings on the effects of p53 on NOX4 in several tumors and examined the basis of NOX4 transcriptional regulation by p53 and SMAD3. Statistical analysis of expression data from primary tumors ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…BET inhibition blocks the enrichment of transcriptional components (H4K16ac, Brd4, and p300) associated with the Nox4 promoter. Previously, we demonstrated that Nox4 transcription is associated with an active histone mark, H4K16ac (10), whereas inactivated p300 has been reported to reduce Nox4 expression in cancer cells (33). We examined whether decreased Nox4 gene expression by the BET inhibitor, OTX015, was due to the reduction of these transcriptional components at the Nox4 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…BET inhibition blocks the enrichment of transcriptional components (H4K16ac, Brd4, and p300) associated with the Nox4 promoter. Previously, we demonstrated that Nox4 transcription is associated with an active histone mark, H4K16ac (10), whereas inactivated p300 has been reported to reduce Nox4 expression in cancer cells (33). We examined whether decreased Nox4 gene expression by the BET inhibitor, OTX015, was due to the reduction of these transcriptional components at the Nox4 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…We report here that Brg1 may rely on its interaction with the histone acetyltransferase p300 to activate NOX4 transcription and ROS production. Leto and colleagues have previously shown that mutant p53 drives NOX4 transcription in a range of different cancer cells via recruiting p300 to acetylate histone H4K8 surrounding the NOX4 promoter (Boudreau et al, 2017). Sanders et al (2015) and Liu et al (2019) have previously reported that up-regulation of NOX4 transcription is accompanied by accumulation of acetylated H4K16, mediated by the acetyltransferase hMOF/MYST1, on the NOX4 promoter in lung fibroblast cells and in hepatocytes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…So far, cell migration was often investigated in cancerous cell lines, e.g., lung and breast epithelial (cancer) cells. In these cells, this phenomenon was reported to be dependent on p53 status [ 24 ], which can be influenced by histone modifications [ 25 ]. However, this might be peculiar for cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In migrating vascular smooth muscle cells, induction of NOX4 and ROS is associated with an activation of focal adhesion kinase (FAK) [ 23 ]. In migrating lung and breast epithelial cells, this phenomenon was reported to be dependent on p53 status [ 24 ], which in turn was tightly regulated by histone modifications [ 25 ]. These data indicate that NOX4 may be a key regulator of cell migration.…”
Section: Introductionmentioning
confidence: 99%